2019
DOI: 10.1108/ijssp-11-2018-0208
|View full text |Cite
|
Sign up to set email alerts
|

Zakat and waqf as instrument of Islamic wealth in poverty alleviation and redistribution

Abstract: PurposeZakat has a strong humanitarian and social-political value. Zakat occupies a central role in Islamic fiscal policy and operations. At the same time, it does not preclude the use of modern tools and techniques in raising the state revenues. Islam provides its own comprehensive approach how the state can raise its revenue and how the revenue should be spend. Zakat is collected from those who are qualified and distributed to the eight recipients as identified in the Quran. Waqf instrument plays an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 2 publications
3
42
0
5
Order By: Relevance
“…On the other hand, commercial competence is very important to reach the purpose of Waqf institutions to make Waqf assets productive in relation with the productivity of Waqf assets which is finally expected to increase wealth for all Muslims and people generally. This is in line with Razak (2019) that Waqf has a role in increasing, preserving and generating wealth by utilizing Waqf assets to earn more income, which is beneficial for the development of Islam and the entire Ummah. In addition, Suhaimi and Suhaimi (2020) explained that Waqf also has a position in economics when all sources and Waqf assets can be used for the benefits of society.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, commercial competence is very important to reach the purpose of Waqf institutions to make Waqf assets productive in relation with the productivity of Waqf assets which is finally expected to increase wealth for all Muslims and people generally. This is in line with Razak (2019) that Waqf has a role in increasing, preserving and generating wealth by utilizing Waqf assets to earn more income, which is beneficial for the development of Islam and the entire Ummah. In addition, Suhaimi and Suhaimi (2020) explained that Waqf also has a position in economics when all sources and Waqf assets can be used for the benefits of society.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, Nurzaman (2017) found that productive zakat that is distributed increases the mustahiq welfare index both in material and spiritual terms. Other research such as those conducted by Sari et al (2019) and Razak (2020) also show the same result. However, Afriadi and Sanrego (2016) found that overlapping distribution with government programs is one of the priority problems of the Zakat Institution, making distribution less effective and efficient.…”
Section: Introductionsupporting
confidence: 78%
“…As the guidelines recommend, a company may increase a maximum of MYR3m in a year irrespective of the number of ventures and a total of MYR5m on the equity platform (SCM, 2015). This is a good prospect for energetic investors to embark upon sustainable business ventures (Razak, 2020). As for Islamic equity crowdfunding, while currently there is only one registered Islamic equity crowdfunding platform, many other platforms also offer Islamic practices without registering their company as Islamic.…”
Section: Literature Reviewmentioning
confidence: 99%